Մատենադարանի՝ հայոց ցեղասպանության մասին արխիվային վավերագրերը - Սահակյան, Վերա («Նաիրի» հրատ.)
В Матенадаране им. Маштоца хранятся документы, отнo-сящиеся к геноциду армян. Это различные докладные записки, сви-детельства очевидцев, мемуары, дневники, официалные османские документы, отчеты об организации различных мероприятий с целью помощи армянским сиротам и беженцам и т. д. Эти материалы входят в состав сборникa архивных документов католикосов, в фонды попечительства армянских церквей Новой Нахичевани, Католикоса Всех Армян Мкртича I (1893-1907 гг.), архимандрита Тирайра, филолога Норайра Бюзандаци (1844-1916), историка А. Алпояджяна и др. Среди них есть документы на армянском, русском, английском, французском, немецком, армянописьменном турецком, османском (оригиналы и копии, машинописные оригиналы и ко-пии), а также микрофильмы. Matendaran houses a number of documents related to the Armenian Genocide (1894-1923). They include reports about Armenian-populated areas and the Armenians of Western Armenia and Ottoman Turkey, eyewitness accounts, memoires, diaries, and records of different initiatives aimed at supporting Armenian orphans and migrants, official documents of the Ottoman Empire, etc. The documents are part of the Archive of the Catholicoi, the collections of the trustees of the Armenian Churches of New-Nakhijevan, including Catholicos Mkrtich I Vanetsi (1893-1907), Vardapet Tirayr, philologist Norayr Byuzandatsi, A. Alboyadjian and others. They are in Armenian, Russian, English, French, German, Turkish in Armenian letters, Ottoman (originals, copies, type-written originals and copies) as well as microfilms.
Keywords: Մատենադարանի հավաքածու; Պատմագրություն; Հայոց ցեղասպանություն